Evaluating cryptocurrency laundering as a complex socio-technical system: A systematic literature review. Issue 3 (2nd July 2019) - Desmond, Dennis B.; Lacey, David; Salmon, Paul
Abstract : Purpose: The purpose of this paper is to present the findings from a literature review, which aimed to identify previous studies evaluating cryptolaundering from a systems thinking perspective. The aim of this paper is to first confirm that cryptolaundering systems can indeed be defined as complex socio-technical systems and second to present the findings from a systematic review of the literature to determine the extent to which previous research has adopted a systems thinking perspective. Design/methodology/approach: The study involved a SLR of studies published in the peer-reviewed literature between 2009 and 2018. Rasmussen's risk management framework (Rasmussen, 1997 ) was used to evaluate the extent to which a systems thinking perspective had been adopted. Findings: The cryptolaundering process is considered to be a complex socio-technical system. The review demonstrates that no previous studies have defined cryptolaundering as a complex socio-technical system or used systems thinking framework approach to evaluate how criminals, regulatory bodies or law enforcement entities understand processes and assess risk within cryptolaundering systems. It is argued that using such an approach to the cryptolaundering process would likely improve assessing criminal risk analyses of cryptolaundering and assist law enforcement and regulatory bodies with understanding risk management during the laundering of cryptocurrencies. Originality/value: Future assessments of cryptolaundering using socio-technical system analytical processes may afford law enforcement and regulatory bodies the opportunity to improve intervention techniques and identify gaps in regulations and enforcement.